Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.psychres.2016.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and characterization of mania: Quantifying increased energy and activity in the human behavioral pattern monitor

Abstract: Increased energy or activity is now an essential feature of the mania of Bipolar Disorder (BD) according to DSM-5. This study examined whether objective measures of increased energy can differentiate manic BD individuals and provide greater diagnostic accuracy compared to rating scales, extending the work of previous studies with smaller samples. We also tested the relationship between objective measures of energy and rating scales. 50 hospitalized manic BD patients were compared to healthy subjects (HCS, n=39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…A significant association between periodontitis and depression was previously demonstrated, 10,[13][14][15][16] noted that the criteria used to define periodontitis may influence the prevalence presented in different studies. 1 In the present study, the Findings from the present study showed no significant differences in the occurrence of known risk variables for periodontitis (e. g. smoking, diabetes, gender, and family income) between individuals with and without BAPD. A possible explanation can be the homogeneity of the sample groups.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…A significant association between periodontitis and depression was previously demonstrated, 10,[13][14][15][16] noted that the criteria used to define periodontitis may influence the prevalence presented in different studies. 1 In the present study, the Findings from the present study showed no significant differences in the occurrence of known risk variables for periodontitis (e. g. smoking, diabetes, gender, and family income) between individuals with and without BAPD. A possible explanation can be the homogeneity of the sample groups.…”
Section: Discussioncontrasting
confidence: 45%
“…Periodontitis is highly prevalent with varying patterns in different populations. However, it should be noted that the criteria used to define periodontitis may influence the prevalence presented in different studies . In the present study, the use of the criteria by Gomes‐Filho et al to the detriment of the current criteria proposed by the CDC/AAP was motivated by the fact that the first also includes BOP and by the high occurrence of CAL in our sample (which does not necessarily indicate periodontitis).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Twenty-six (16 male, 10 female, 22 Caucasian) acutely hospitalized inpatients with SCID (Structured Clinical Interview for DSM-IV)-diagnosed “DSM-IV Bipolar Disorder, Current Episode Manic” provided informed consent and participated in this study. Reports of hBPM differences between manic BD patients and healthy comparison participants can be found in our previously published work [14,17,18]; the participants in the current study were a subsample for which we had COMT genotypes available. Participants were between the ages of 18 and 55 years (mean age = 35.2, standard deviation = 13.0).…”
Section: Methodsmentioning
confidence: 99%
“…When the oscillations of mood are very marked with alternation of cycles, and go from great happiness to profound sadness, it is called cyclothymia. The alternation phases of depression with phases of mania characterize the BPAD, even though higher predominance and chronicity on stages of depression are observed [18,19] (Figure 3).…”
Section: Introductionmentioning
confidence: 99%